THE INFLUENCE OF WORK ENGAGEMENT, JOB SATISFACTION, AND ORGANISATIONAL CITIZENSHIP BEHAVIOR ON EMPLOYEE PERFORMANCE FAIZAM CONCRETE SUGIO LAMONGAN - M. Gilang Maulana Sti’ady; Lilik Nurcholidah (RTTM, 2025)
This study aims to determine the effect of work engagement, job satisfaction, and organizational citizenship behaviour on employee performance (case study on employees at faizam concrete sugio lamongan). This type of research is quantitative research. The population of this research is all employees at faizam concrete and to determine the number of samples the researcher uses a sample technique so that 40 samples are obtained. Data collection in this study is through surveys to locations and distributing questionnaires. The data collected was then processed using SPSS version 26. The data analysis method uses validity and reliability tests, classical assumption tests, multiple linear regression and t tests (partial regression coefficient tests). The results of the study indicate that work engagement partially has no effect on employee performance, while job satisfaction and organizational citizenship behaviour (OCB) partially affect employee performance.